2018
DOI: 10.3390/bs8050051
|View full text |Cite
|
Sign up to set email alerts
|

Protective Activity of Erythropoyetine in the Cognition of Patients with Parkinson’s Disease

Abstract: Introduction: Treatment strategies in Parkinson’s disease (PD) can improve a patient’s quality of life but cannot stop the progression of PD. We are looking for different alternatives that modify the natural course of the disease and recent research has demonstrated the neuroprotective properties of erythropoietin. In Cuba, the Center for Molecular Immunology (CIM) is a cutting edge scientific center where the recombinant form (EPOrh) and recombinant human erythropoietin with low sialic acid (NeuroEPO) are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Another reason to use the latent variables is to reduce the ceiling-floor effect of global screening tools such as the MMSE and the DRS, which were included, first, because MMSE is the most well-known psychometric test used to describe cognitive aging and second because the Movement Disorder Society has recommended the DRS to study cognition in PD 34 . Our preliminary report found 18 cognitive improvements in several tests (FAB, DRS, Rey figure copy and recall) in both groups (Placebo and NeuroEPO) when comparing baseline with one week and six months after the intervention. In our opinion, this could be explained partially because the first timepoint, only six weeks after the baseline, was influenced by practice and learning effects.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Another reason to use the latent variables is to reduce the ceiling-floor effect of global screening tools such as the MMSE and the DRS, which were included, first, because MMSE is the most well-known psychometric test used to describe cognitive aging and second because the Movement Disorder Society has recommended the DRS to study cognition in PD 34 . Our preliminary report found 18 cognitive improvements in several tests (FAB, DRS, Rey figure copy and recall) in both groups (Placebo and NeuroEPO) when comparing baseline with one week and six months after the intervention. In our opinion, this could be explained partially because the first timepoint, only six weeks after the baseline, was influenced by practice and learning effects.…”
Section: Discussionmentioning
confidence: 69%
“…This molecule is similar to that produced in the brain of mammals but does not have an inducer effect in the synthesis of erythrocytes, maintaining its neuroprotective properties. NeuroEPO is safe and tolerated in healthy people 13 and PD patients 14 , but its neuroprotective effects have been mainly tested in animal models 15,16 , in-vitro models 17 , and partially reported 18 on the cognitive performance of PD patients. But this is the first attempt to study the long-term effects of cognitive effects of NeuroEPO in PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, neuro-EPO improved cognitive functions in PD patients. Another clinical trial phase III with neuro-EPO treatment for PD patients is in progress to confirm its neuroprotective properties ( Pedroso et al, 2018 ). The preliminary results showed that nasally administered neuro-EPO for 5 weeks in patients with PD stages 1 and 2 on the Hoehn & Yahr Scale was well-tolerated ( García-Llano et al, 2021 ).…”
Section: Epo Derivative Treatment For Ischemic Strokementioning
confidence: 99%
“…In human, a first evaluation on healthy human volunteers 27 indicated that 0.5 and 1 mg of Neuro‐EPO every 8 h during 4 days were well tolerated and had no erythropoiesis effect. More clinical trials at similar dosage are ongoing against stroke (acute treatment 1‐mg Neuro‐EPO by nasal route every 8 h for 3 days) and against long‐term neurodegenerative disease on mild–moderate Alzheimer patients and Parkinson patients 28,29 . In these human trials, the daily dose administered correspond to several dose of 13 μg/kg (for a man with a mean 75 kg body weight), which is close to the 40 μg/kg single dose administered to rats in this work.…”
Section: Detection After a Single In Administrationmentioning
confidence: 99%